I posted an inequality few days ago, but I realized later on that it could only holds under stronger constraints. In particular I reduced such inequality to the inequality I am posting here. I think it is nice and I would really pleased if someone could give me any some suggestion. I simulated it with million of combinations and it always held. Thanks in advance!

Consider two tuples each of $n$ positive real numbers $(x_1, x_2, ...x_n)$ and $(y_1,y_2,...,y_n)$ and two real numbers $q \in (0,1)$ and $\beta \in (0,1)$. If $$ \sum_{i=1}^n{\frac{q}{\beta x_i}} = \sum_{i=1}^n{\frac{1-q}{(1-\beta) y_i}}, $$ is it true that the inequality below holds?$$ \sum_{i=1}^n{\frac{q}{\beta x_i}} \geq \sum_{i=1}^n{\frac{1}{\beta x_i + (1-\beta) y_i}}. $$

  • $\begingroup$ Is there a typo? $q=0$ is a counterexample to both the equality and the inequality. $\endgroup$ – Stella Biderman Feb 18 '18 at 16:00
  • $\begingroup$ The equality seems to be a given condition. $\endgroup$ – Saad Feb 18 '18 at 16:02
  • $\begingroup$ @enricopiovano Your proposed inequality has nothing to do directly with the three inequalities you tagged, please don't misuse tags. $\endgroup$ – Saad Feb 18 '18 at 16:04
  • $\begingroup$ @AlexFrancisco : thanks a lot to let me know, I am very sorry $\endgroup$ – Enrico Piovano Feb 18 '18 at 16:09
  • $\begingroup$ @StellaBiderman for $q=0$, may consider $\beta=0$ and find an undertermined form. However, you are completely right, it is better to consider both $q \in (0,1)$ and $\beta \in (0,1)$. Let me modify the exercise. AlexFrancisco is completely right. the equality gives you a condition, and based on the condition you need to prove the inequality. $\endgroup$ – Enrico Piovano Feb 18 '18 at 16:15

By Cauchy's inequality,$$ (βx_k + (1 - β)y_k)\left( \frac{q^2}{βx_k} + \frac{(1 - q)^2}{(1 - β)y_k} \right) \geqslant (q + (1 - q))^2 = 1, $$ i.e.$$ \frac{q^2}{βx_k} + \frac{(1 - q)^2}{(1 - β)y_k} \geqslant \frac{1}{βx_k + (1 - β)y_k}. \quad 1 \leqslant k \leqslant n $$

Note that$$ \sum_{k = 1}^n \frac{q}{βx_k} = \sum_{k = 1}^n \frac{1 - q}{(1 - β)y_k}, $$ thus \begin{align*} \sum_{k = 1}^n \frac{q}{βx_k} &= q \cdot \sum_{k = 1}^n \frac{q}{βx_k} + (1 - q) \cdot \sum_{k = 1}^n \frac{1 - q}{(1 - β)y_k}\\ &= \sum_{k = 1}^n \left( \frac{q^2}{βx_k} + \frac{(1 - q)^2}{(1 - β)y_k} \right)\\ &\geqslant \sum_{k = 1}^n \frac{1}{βx_k + (1 - β)y_k}. \end{align*}

  • $\begingroup$ This is a very elegant solution ! Really thanks a lot @AlexFrancisco, very very appreciated. $\endgroup$ – Enrico Piovano Feb 19 '18 at 22:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.